Prêmio salarial urbano e a trajetória da desigualdade: Evidências paro o Brasil - Bruno de Oliveira Cruz; Paolo Naticchioni (Instituto de Pesquisa Econômica Aplicada (IPEA), 2012)
– In this paper, we use data from the National Household Survey (PNAD) for Brazil to investigate the dynamics of the urban wage premium and the relationship between the urban wage premium and inequality trends, and we find two main results. First, we find a decreasing urban wage premium over the period 2002-2009 using both OLS and quantile regression. Second, we show that the fall in the urban wage premium is more pronounced at the 90th percentile than at the 10th percentile. This finding suggests that the falling urban wage premium has contributed to the reduction in inequality observed in Brazil in the last decade.
Keywords: J31; J61; R23; 330; urban wage premium; wage inequality; Brazil; Regionale Lohnstruktur; Brasilien